Overweight is associated to a better prognosis in metastatic colorectal cancer: A pooled analysis of FFCD trials. (July 2018) - ,; Adenis, A.; Alessio, A.; Aouakli, A.; Azzedine, A.; Bedjaoui, A.; Bidault, A.; Blanchi, A.; Botton, A.; Cadier-Lagnes, A.; Fatisse, A.; Gagnaire, A.; et al.
Abstract: Background: Previous studies showed that high and low body mass index (BMI) was associated with worse prognosis in early-stage colorectal cancer (CRC), and low BMI was associated with worse prognosis in metastatic CRC (mCRC). We aimed to assess efficacy outcomes according to BMI. Patients and methods: A pooled analysis of individual data from 2085 patients enrolled in eight FFCD first-line mCRC trials from 1991 to 2013 was performed. Comparisons were made according to the BMI cut-off: Obese (BMI ≥30), overweight patients (BMI ≥ 25), normal BMI patients (BMI: 18.5–24) and thin patients (BMI <18.5). Interaction tests were performed between BMI effect and sex, age and the addition of antiangiogenics to chemotherapy. Results: The rate of BMI ≥25 patients was 41.5%, ranging from 37.6% (1991–1999 period) to 41.5% (2000–2006 period) and 44.8% (2007–2013 period). Comparison of overweight patients versus normal BMI range patients revealed a significant improvement of median overall survival (OS) (18.5 versus 16.3 months, HR = 0.88 [0.80–0.98] p = 0.02) and objective response rate (ORR) (42% versus 36% OR = 1.23 [1.01–1.50] p = 0.04) but a comparable median progression-free survival (PFS) (7.8 versus 7.2 months, HR = 0.96 [0.87–1.05] p = 0.35). Subgroup analyses revealed that overweight was significantly associated with better OS in men. OS and PFS were significantly shorter in thin patients. Conclusion: Overweight patients had a prolonged OS compared with normal weight patients with mCRC. The association of overweight with better OS was only observed in men. The pejorative prognosis of BMI <18.5 was confirmed. Highlights: Body mass index of patient enrolled in clinical trial increases across the time period. Overweight patients had a prolonged overall survival compared with normal weight patients. The association of overweight with better OS was only observed in men. Thin patients had a worst overall survival compare to normal weight patients.